2010
DOI: 10.17221/2979-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an aerobic training program on oxidative stress biomarkers in bulls

Abstract: ABSTRACT:The aim of this study was to evaluate the effect of aerobic training (16 weeks -T1 and 24 weeks -T2) on oxidative stress biomarkers. To this end, GSH, GSH-peroxidase (GSH-Px) and catalase (CAT) activity were analysed in plasma. Nine bulls (3-4 years), were included in this work. The exercise training protocol was performed in a track ("taurodromo") three days per week for 24 weeks and consisted of 400 m warming up, 1200 m to 4-5 m/s, two minutes' resting, 1200 m to 4-5 m/s and, finally, 400 m walking.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
7
1
2
Order By: Relevance
“…Los factores limitantes del toro durante la lidia se pueden resumir en disminución de la volemia y número de glóbulos rojos, lesión muscular, deshidratación, fatiga, acidosis y fuerte depleción del glucógeno muscular, entre otros (Agüera Buendía y Requena Domenech, 2011). Esto hizo pensar a los ganaderos en entrenar al toro bravo antes del espectáculo como método de aumento de su eficiencia en plaza, no obstante, la poca bibliografía existente arroja resultados dispares (Escribano et al, 2010;Requena, 2012). Escalera-Valente et al (2008) por su parte, estudiaron el efecto de la lidia sobre los gases sanguíneos, cuyas concentraciones reflejaron una inadaptación del animal al ejercicio llevado a cabo en el ruedo, aun habiendo sido entrenados físicamente antes del festejo.…”
Section: Discussionunclassified
“…Los factores limitantes del toro durante la lidia se pueden resumir en disminución de la volemia y número de glóbulos rojos, lesión muscular, deshidratación, fatiga, acidosis y fuerte depleción del glucógeno muscular, entre otros (Agüera Buendía y Requena Domenech, 2011). Esto hizo pensar a los ganaderos en entrenar al toro bravo antes del espectáculo como método de aumento de su eficiencia en plaza, no obstante, la poca bibliografía existente arroja resultados dispares (Escribano et al, 2010;Requena, 2012). Escalera-Valente et al (2008) por su parte, estudiaron el efecto de la lidia sobre los gases sanguíneos, cuyas concentraciones reflejaron una inadaptación del animal al ejercicio llevado a cabo en el ruedo, aun habiendo sido entrenados físicamente antes del festejo.…”
Section: Discussionunclassified
“…Despite the effects of exercise on health benefits, many studies reported during exhausting physical exercise there is an ischemia-reperfusion process that causes the production of oxidative due to release it of electrons from the respiration chain. During exhausting physical exercise, the release of free radicals can increase in mitochondria and cause oxidative stress (Daniel et al, 2010;Escribano et al, 2010). Oxidative stress causes DNA damage, loss of protein structure function such as membrane enzymes and receptors, and structural damage from the lipid cell layer (Guzel et al, 2007;Abruzzo et al, 2013;Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies on the effect of training on the physiology of the bull [85][86][87]; however, we can state that training potentially increases athletic performance, as can be deduced from muscular and blood metabolic adaptations [88,89]. It has been observed that training favors the β-oxidative metabolic pathway of fatty acids (oxidative metabolism) prevailing over the glycolytic pathway, requiring a protocol of at least 6 months to increase its antioxidant capacity [89,90].…”
Section: Falling Syndromementioning
confidence: 99%